2022
DOI: 10.32530/jace.v5i1.449
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Mapping Analysis and Description of Conflict over Oil Palm Plantation Land between the Community of Senama Nenek Village and PTPN V Sei Kencana in Kampar Regency

Abstract: The conflict in the plantation sector involving the community and the company in the Senama Nenek Village occurred because of a dispute of an area of ??± 2,800 hectares which had been acknowledged by both parties, the people of Grandma Senama Village and PTPN V Sei Kencana. This difference in opinion caused the public to make complaints to local governments. This study aims to overcome plantation conflicts and describe plantation conflicts that occur between the people of Senama Nenek Village and PTPN V Sei Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, the Minister of SOEs and Commission VI of the House of Representatives of the Republic of Indonesia stated that they refused to hand over the area and suggested that the settlement of disputed land be resolved through legal channels. [4] On November 28, 2007, a meeting was held at the Arya Duta Pekanbaru hotel to discuss the land dispute between Senama Nenek Community and PTPN V. This meeting resulted in several points, namely: [3] a. Agree on the settlement of plantation cases on customary land; b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Minister of SOEs and Commission VI of the House of Representatives of the Republic of Indonesia stated that they refused to hand over the area and suggested that the settlement of disputed land be resolved through legal channels. [4] On November 28, 2007, a meeting was held at the Arya Duta Pekanbaru hotel to discuss the land dispute between Senama Nenek Community and PTPN V. This meeting resulted in several points, namely: [3] a. Agree on the settlement of plantation cases on customary land; b.…”
Section: Methodsmentioning
confidence: 99%
“…[3] The mediation was held on July 16, 2012, attended by representatives of Senama Nenek community, village apparatus, House of Representative of Kampar regency, and PTPN V themselves where both parties, Senama Nenek community and PTPN V, have agreed to solve this tenurial dispute through cooperative scheme known as Kredit Kepada Koperasi Primer untuk Anggotanya (KKPA) or Credit to Primary Cooperatives for Their Members. [6] Kredit Kepada Koperasi Primer untuk Anggotanya (KKPA) or Credit to Primary Cooperatives for Their Members is a form of credit scheme with soft terms provided by the government through PT (Persero) Permodalan Nasional Mandiri (PT. PNM) to primary cooperatives which are then distributed to their members where KKPA distribution with partnership programs is a must, because the KKPA scheme requires a plasma-core pattern.…”
Section: Methodsmentioning
confidence: 99%